The acute effect of concurrent training on running performance over 6 days - Doma, K.; Deakin, G. (Research Quarterly for Exercise and Sport, 2015)
Purpose: This study examined the effects of strength training on alternating days and endurance training on consecutive days on running performance for 6 days. Methods: Sixteen male and 8 female moderately trained individuals were evenly assigned into concurrent-training (CCT) and strength-training (ST) groups. The CCT group undertook strength training on alternating days combined with endurance training on consecutive days for 6 days. One week later, the CCT group conducted 3 consecutive days of endurance training only to determine whether fatigue would be induced with endurance training alone (CCT-Con). Endurance training was undertaken to induce endurance-training stimulus and to measure the cost of running (CR), rating of perceived exertion (RPE), and time to exhaustion (TTE). The ST group undertook 3 strength-training sessions on alternating days. Maximal voluntary contraction (MVC), rating of muscle soreness (RMS), and rating of muscle fatigue (RMF) were collected prior to each strength and endurance session. Results: For the CCT group, small differences were primarily found in CR and RPE (ES = 0.17-0.41). However, moderate-to-large reductions were found for TTE and MVC (ES = 0.65-2.00), whereas large increases in RMS and RMF (ES = 1.23-2.49) were found prior to each strength- and endurance-training session. Small differences were found in MVC for the ST group (ES = 0.11) and during CCT-Con for the CCT group (ES = 0.15-0.31). Conclusion: Combining strength training on alternating days with endurance training on consecutive days impairs MVC and running performance at maximal effort and increases RMS and RMF over 6 days.